Political challenges for China at the beginning of the 21st century - A. V. Vinogradov (Сравнительная политика, 2017)
The Chinese economic model, which paved the way to «Chinese economic miracle» is running out of its capabilities. The new generation of leadership led by Xi Jinping is facing an extremely complicated task that can be compared to the one Deng Xiaoping had solved at the turn of 1980’s – to elaborate a new model of development. Measures adopted by the new General secretary of the CPC Central Committee in order to concentrate powers and to strengthen personal power are justifi ed by the need to change political course. However, as a result of these steps, the system of institutional authoritarianism that for the past 40 years was being created and provided economic success to China has been signifi cantly demolished. Current challenges for China originate not only from the necessity to change the economic model, but also from the reaction of the authorities to this need. Amidst uncertainty of new reference points for the reforms, lack of obvious competitive advantages, strengthening of external challenges and deep changes in Chinese society, China has again appeared on the verge of serious challenges, the answer to which will help evaluate the effectiveness of the reforms not only from socio-economic but also from a historical perspective.